Seemingly altruistic behavior and strategic ignorance in a dictator game with potential loss - Yamamoto, Keisuke; Hashimoto, Hirofumi (Frontiers in Psychology, 2025)
Previous studies have indicated that in the standard binary version of the dictator game, people are less likely to behave altruistically when given the opportunity to be strategically ignorant. The present study aims to assess the robustness of individuals’ strategic ignorance in the context of the emergence of empathic concern. It is reasonable to hypothesize that traditional standard dictator games may not be an optimal context for the emergence of empathic concern. Accordingly, the purpose of the present study is to use a dictator game with loss potential that facilitates player empathic concern to investigate the emergence of (seemingly) altruistic behavior and strategic ignorance in the context of empathy. The results of a web experiment with 200 Japanese adults showed that our manipulation of loss had no effect on the occurrence of altruistic behavior and strategic ignorance. Moreover, even in situations in which the participant, as a dictator, is aware that the recipient has suffered a loss, they behave as if they have a legitimate reason not to act altruistically by being strategically ignorant. This result demonstrates the robustness of strategic ignorance and indicates that evoking empathic concern may not have enough of an effect to influence altruistic behavior in the laboratory experiment.